A Cross-Sectional Study On the Preferences and Perception of MBBS Students Regarding Various Teaching Methods in A Medical College in South India - Kumar Reddy, S. Bhavadeep; .R, Ramya; Brahmaiah, Jyoti; Deepthi, C. Sravana; Rajasekhar, P.; Kumar, P. Vijay (Journal of Neonatal Surgery, 2025)
Medical education is increasingly shifting towards learner-centered methods, emphasizing interactive methods. The introduction of Competency-Based Medical Education in our country has prompted the exploration of students' preferences and perceptions regarding various teaching methods to optimize curriculum design and improve learning outcomes. Present study assessed the preferences and perceptions of MBBS students regarding various teaching-learning methods and their effectiveness at medical colleges in South India. A cross-sectional study involved 300 MBBS students from the 1st and 2nd Phases. A structured and validated questionnaire was used to gather data on demographics, preferences for teaching methods, and perceptions of their effectiveness. Statistical analysis was performed using descriptive statistics and chi-square tests. The study found that problem-based learning (PBL) was the preferred teaching method (72.6% approval), followed by small group discussions (SGDs), with 69.9% approval. Traditional didactic lectures received a neutral response from the majority of students. Regarding teaching aids, models, charts, and specimens were highly favored, with 80.5% approval. Students expressed better focus and interaction during PBL and SGDs than didactic lectures. The ideal session duration was 40-45 minutes, which 85.4% of students preferred. The study also highlighted that 71.4% of students were unaware of newer teaching methods, indicating a communication gaps regarding modern educational strategies. Our study highlights the preference for interactive teaching methods such as PBL and SGDs over traditional lectures. There is a need for awareness and communication improvement about innovative teaching methods. Thus, enhanced curriculum and trained faculty are needed accordingly to meet the evolving needs of medical students.